Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.4 Financial Sector - Insurance - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to gain an understanding of the financial reporting requirements for insurance companies in a jurisdiction in addition to or instead of the requirements for commercial enterprises in general. Unless otherwise stated, the term insurance company refers to both insurance and reinsurance companies. There are also questions in relation to the monitoring and enforcement capacity of the local insurance supervisor in respect of financial reporting of insurance companies specifically. Questions are based on the internationally recognized insurance core principles issued by the International Association of Insurance Supervisors. The report is structured as follows: overview of the insurance sector; financial reporting requirements for insurance companies; statutory audit and other forms of independent assurance; audit committees; filing and publication of financial statements; monitoring and enforcement: financial reporting; and corporate governance.